Genetic variability in tissue culture: Impact on germplasm conservation and utilization - Scowcroft, W.R. (1984)
This technical report looks at in vitro culture techniques, in vitro germplasm storage, variability from in vitro culture, factors influencing somaclonal variation, origin of tissue culture instability and somaclonal variation and the impact of culture instability and somaclonal variation.